2020
DOI: 10.1038/s41467-020-16552-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific fibroblast subpopulations and neuronal structures provide local sources of Vegfc-processing components during zebrafish lymphangiogenesis

Abstract: Proteolytical processing of the growth factor VEGFC through the concerted activity of CCBE1 and ADAMTS3 is required for lymphatic development to occur. How these factors act together in time and space, and which cell types produce these factors is not understood. Here we assess the function of Adamts3 and the related protease Adamts14 during zebrafish lymphangiogenesis and show both proteins to be able to process Vegfc. Only the simultaneous loss of both protein functions results in lymphatic defects identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 69 publications
2
69
1
Order By: Relevance
“…Likewise, loss of the Vegfc-processing components adamts3 and adamts14 in zebrafish also mimicked the vegfc mutant phenotype exhibiting absent trunk, facial and meningeal lining lymphatics (Wang et al, 2020).…”
Section: Embryonic Development Of Lymphatic Vesselsmentioning
confidence: 77%
See 1 more Smart Citation
“…Likewise, loss of the Vegfc-processing components adamts3 and adamts14 in zebrafish also mimicked the vegfc mutant phenotype exhibiting absent trunk, facial and meningeal lining lymphatics (Wang et al, 2020).…”
Section: Embryonic Development Of Lymphatic Vesselsmentioning
confidence: 77%
“…A disintegrin and metalloproteinase with thrombospondin motifs 3 (ADAMTS3) is a VEGF-C protease, whose total deletion (i.e., Adamts3 –/– mice) mirrored the phenotypes observed in Ccbe1 and Vegfc null embryos ( Bui et al, 2016 ). Likewise, loss of the Vegfc-processing components adamts3 and adamts14 in zebrafish also mimicked the vegfc mutant phenotype exhibiting absent trunk, facial and meningeal lining lymphatics ( Wang et al, 2020 ).…”
Section: Embryonic Development Of Lymphatic Vesselsmentioning
confidence: 85%
“…Prior studies have shown that Ccbe1, Adamts3, and Adamts14 serve to proteolytically cleave and convert the pro-active form of Vegfc into its mature form during lymphangiogenesis in zebrafish ( Hogan et al, 2009 ; Le Guen et al, 2014 ; Wang et al, 2020 ). Among these three proteins, ccbe1 appears to be highly expressed in the developing brain and meningeal compartments based on its BAC transgenic reporter expression at 48 hpf ( Wang et al, 2020 ), while adamts3 BAC transgenic reporter expression appear to be very low at the same stage. Since 48 hpf is a developmental time point when the DLV is extending toward the mCP, ccbe1 could be a strong candidate that acts to activate Vegfc in this area of the brain.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in ADAMTS14 have been associated with delayed onset of Achilles tendon pathology and increased risk for OA 80‐82 . In a recent study in zebrafish, it was demonstrated that both, ADAMTS3 and ADAMTS14 can process VEGF‐C and that inactivation of both proteases was required to elicit a lymphatic phenotype 83 . This suggests that, in contrast to mice and humans, ADAMTS14 can cleave VEGF‐C and compensate for the loss of ADAMTS3 in zebrafish.…”
Section: Adamts Protease and Their Substrates In Musculoskeletal Devementioning
confidence: 99%